Devastating extreme Mediterranean cyclone’s impacts in Turkey - Sirdas, Sevinc A.; Tuncay Özdemir, E.; Sezen, İsmail; Efe, Bahtiyar; Kumar, Vinay (Springer Science and Business Media LLC, 2017)
A tropical cyclone was formed over central northern Africa near Egypt, Libya and Crete, and it moved and deepened toward the north–northeast; meanwhile, the storm destroyed many regions in the west, southwest and central of Turkey. The cyclone carried huge dust from the north of Africa to Turkey and reduced the visibility to less than 1 km and raised the wind speed. As a result of severe storm, some meteorological stations have new extreme values that the strongest wind speed measured was 81 knots in the central region of Turkey. Medicane with wind speed 81 knots especially over Turkey is a rare event. This devastating cyclone carried exceptionally very strong winds (>80 kts) with favorable conditions to follow windstorm conceptual model. The cyclone caused adverse conditions such as excessive injuries, fatal incidents and forest fires. Mesoscale vortex formed and affected particularly the middle and western regions of Turkey. The vertical thermodynamic structure of storm is compared with April values of 40 years of datasets over Istanbul. Moreover, four different winds {measurement masts} of Istanbul Ataturk Airport are used for the microscale analysis of different meteorological parameters during deepened pressure level. In addition, divergence and vorticity of stormy weather are discussed in details during the effective time period of storm by solving equations and validated using ERA-40 reanalysis. We obtained many monitoring data sources such as ground base, radar, radiosonde and satellite display the values of the intensity of wind speed caused by cyclones of tropics have revealed similarities.